Socio-Economic and Demographic Determinants of Women Participation in Labor Force in Rural Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2020)
This attempt was made to investigate the socio-economic and demographic factors that influence women participation in labor force in rural Bangladesh using BDHS 2014 data. A total of 11,695 married women aged 15 - 49 in rural areas are selected for analysis. A logistic regression analysis is applied for determining the factors. The result shows that 32.2% rural women are currently employed and the remaining 67.8% are unemployed. The logistic model shows that women’s age has a strong positive association with their participation in labor force. Participation of widowed and divorced/separated women in labor force is much higher as compared to married women. Enhanced education level of women and their husband has decreased women participation in labor force, but it gradually increased with increased education level of household head. Husband’s occupation is a strong determinant of women participation in labor force. Women from middle income households are less interested to participate in labor force as compared to poor women. The result also reveals that with increased household size and number of children under age five, women participation in labor force is decreased. Again, with increased land and livestock ownership of household and NGO membership, women participation in labor force is highly increased.J. Asiat. Soc. Bangladesh, Sci. 46(1): 103-115, June 2020